2022-RA-1263-ESGO Phase II randomized BGOG-CX3 trial comparing atezolizumab in combination with doxorubicin versus doxorubicin alone in second-line or later recurrent cervical cancer. (20th October 2022) - Loverix, Liselore; Salihi, Rawand; van Rompuy, Anne-Sophie; Vanderstichele, Adriaan; van Nieuwenhuysen, Els; Baert, Thaïs; Debruyne, Philip; Cornez, Nathalie; Henry, Stéphanie; Neven, Patrick; Han, Sileny; Berteloot, Patrick; et al.
Abstract : Introduction/Background: Single-agent chemotherapies, like doxorubicin, have very modest activity in recurrent cervical cancer (rCC). Recently, anti-programmed-death protein 1 (anti-PD-1) treatment has shown activity in randomized phase III studies in rCC. In the current study we investigated the combination of doxorubicin with an anti-PD-L1 inhibitor atezolizumab (DA), based on the possible synergistic effect, versus doxorubicin (D) alone. Methodology: Prospective open-label, randomized phase II BGOG-cx3 trial (EudraCT2016–000547–14) randomizing 2:1 to doxorubicin (60 mg/m 2 q3 wks) with or without atezolizumab (1200 mg q3wks), respectively. The primary endpoint was progression-free survival (PFS) rate at 9 months. Secondary endpoints included objective response rate (ORR), duration of response (DOR), disease control rate (DCR), overall survival (OS), PFS and safety analysis. Results: 40 patients were randomized between November 2017 and October 2020: 23 vs 17 patients for DA and D, respectively. Baseline characteristics were similar in both arms (total population: squamous cell carcinoma 84%, prior radiochemotherapy 69%, prior anti-VEGF 61%, median prior lines of chemotherapy in advanced/recurrent setting was 1 with range 0–2). There was a tendency towards a longer median PFS of 4.8 and 3.9 months ( figure 1 ) for DA and D, respectively with HR 0.501 (95%CI 0.246–1.017) (p= 0.0558). Similarly, the primary endpoint, PFS rate at 9 months, was numerically higher but failed to reach significance (26% vs 13% for DA and D, respectively (p=0.054)). Median OS was 10.3 and 7.8 months (p= 0.21) for DA and D, respectively. DCR at 24 weeks was 16% (DA)vs 0% (D) (p=0.279). Results according to PD-L1 staining will be presented. Discontinuation and dose reductions of D were similar in both groups. No new safety signals were noted for the combination of DA. Conclusion: Notwithstanding the limited samples size, this study showed a tendency towards a prolonged PFS and OS when doxorubicin was combined with atezolizumab compared with doxorubicin alone in rCC.